Rifabutin and Furazolidone Could Be the Candidates of the Rescue Regimen for Antibiotic-Resistant H. pylori in Korea. (10th July 2019) - Choi, Youn I; Jeong, Sang-Ho; Chung, Jun-Won; Park, Dong Kyun; Kim, Kyoung Oh; Kwon, Kwang An; Kim, Yoon Jae; So, Seol; Lee, Jeong Hoon; Jeong, Jin-Young; Lee, Sun-Mi
Abstract : Background / Aim . In Korea, the rate of Helicobacter pylori ( H. pylori ) eradication has declinedsteadily as a result of increasing resistance to antibiotics, especially dual resistance to clarithromycin and metronidazole. However, microbiological culture data on drug-resistant H. pylori is lacking. This study evaluated the antimicrobial efficacy of candidate antibiotics against resistant H. pylori strains. Methods . After retrospectively reviewing the data from the Helicobacter Registry in Gil Medical Center (GMC) and Asan Medical Center (AMC), along with 4 reference strains, we selected the 31 single- or multidrug-resistant strains. The susceptibility of the H. pylori strains to seven antibiotics (clarithromycin, metronidazole, levofloxacin, amoxicillin, tetracycline, rifabutin, and furazolidone) and minimum inhibitory concentration were tested using the broth microdilution technique. Results . Among 31 antibiotic resistance strains for H. pylori, there were no strains resistant to rifabutin or furazolidone, which had MICs of <0.008 and 0.5 μ g/mL, respectively. Only one tetracycline-resistant strain was found (MIC < 2 μ g/mL). Amoxicillin and levofloxacin were relatively less effective against the H. pylori strains compared to rifabutin or furazolidone (resistance rates 22.6%, 1.9%, respectively). Tetracycline showed the relatively low resistance rates (3.2%) for H. pylori strains. Conclusions . Therefore, along with tetracycline which has already been used as a component for second-line eradication regimen for Helicobacter, rifabutin and furazolidone, alone or in combination, could be used to eradicate antibiotic-resistant H. pylori strains where drug-resistant Helicobacter spp. are increasing.